A Performance Evaluation of Distributed Algorithms on Shared Memory and Message Passing Middleware Platforms - Ahuja, S.P.; Eggen, R.; K. Jha, A. (Informatica)
A Performance Evaluation of Distributed Algorithms on Shared Memory and Message Passing Middleware Platforms